1994
DOI: 10.1136/jcp.47.9.862
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridisation for the identification of Helicobacter pylori in paraffin wax embedded tissue.

Abstract: A method for identifying Helicobacter pyloni using a non-isotopic in situ hybridisation technique is described. A probe generated by polymerase chain reaction (PCR) with primers directed against parts of the Helicobacter pyloni 16SrRNA sequence was used. Paraffin wax embedded gastric biopsy specimens from patients with and without gastritis were hybridised with the probe, and the method was shown to be sensitive and specific for Hpylor. (7 Clin Pathol 1994;47:862-864)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In situ hybridization (ISH) using digoxigenin (DIG)-labeled oligonucleotide probes complementary to unique target sites on the 16S rRNA (rDNA) is a useful method for the detection and identification of microorganisms (Bashir et al 1994, Barrett et al 1997, Kwon & Chae 1999. Specific probes can be designed to locate organisms that cannot be cultured (Hayashi et al 1990, Komminoth & Werner 1997 or visualized by conventional methods, such as viruses (Lewis & Wells 1992), Chlamydiae (Campbell et al 1993) and Mycobacterium paratuberculosis (Hulten et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization (ISH) using digoxigenin (DIG)-labeled oligonucleotide probes complementary to unique target sites on the 16S rRNA (rDNA) is a useful method for the detection and identification of microorganisms (Bashir et al 1994, Barrett et al 1997, Kwon & Chae 1999. Specific probes can be designed to locate organisms that cannot be cultured (Hayashi et al 1990, Komminoth & Werner 1997 or visualized by conventional methods, such as viruses (Lewis & Wells 1992), Chlamydiae (Campbell et al 1993) and Mycobacterium paratuberculosis (Hulten et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We believe the ability to visualize bacilli with this technique could reduce the likelihood of false positive results inherent in other molecular assays. In situ hybridization has been successfully applied to detect various bacteria, including Helicobacter pylori, 12 Haemophilus influenza, 13 and Klebsiella pneumoniae. 14 Recently, Hagen et al 15 reported a fluorescence in situ hybridization technique using a set of oligonucleotide probes for the identification of B. pseudomallei, B. mallei, and B. thailandensis in bacterial cell smears and experimentally infected mouse tissues.…”
mentioning
confidence: 99%
“…13,48 A sensitivity of 77% to 99% has been reported for the detection of H. pylori by histology. 15,23,28,30,37,45,49 Auxiliary methods, including immunohistochemistry, 2,18,30 in situ hybridization 5,22 and the polymerase chain reaction (PCR), 2,9,46,49 have been applied to improve the sensitivity to detect H. pylori in biopsy material. 47 Besides the direct visualization of the bacteria, a characteristic pattern of inflammation including neutrophils, mononuclear cells, as well as lymphoid follicles can be observed by histology; albeit only the detection of the bacteria unequivocally proves the diagnosis.…”
mentioning
confidence: 99%